Frequency of Abdominal Wound Dehiscence /Burst Abdomen in Patients of Laparotomy - Sana Israr, Muhammad Kamran Khan, Anila Farid, Nadia Qaiser, Kalsoom Akhtar, Aisha Jalal, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Wound dehiscence is a surgical problem in which a wound crack along a surgical incision. It is sometimes called wound disruption, wound breakdown or wound separation. Objective: To find out the frequency of abdominal wound dehiscence in patients with laparotomy. Study design: Descriptive cross sectional study. Material and methods: 385 patients having age of 12-70 yrs with sign of laparotomy have participated such that blunt abdominal trauma, fire arm injury and peritonitis. Patients had been admitted in the surgical unit. After comprehensive history, complete physical and systematic examination have been done. Data was analyzed using SPSS version 10.0.For indication of laparotomy and wound dehiscence, frequency and percentage were presented. Result: 263 male (68.31%) and 122 female (31.69) participated in study. Mean age was 35.72 ±12.732. About 4.42% (n=17) patients had abdominal wound dehiscence. In 12-30 years age group, 4/152 patients had abdominal wound dehiscence. Among the age group 31-50 years,7/177 patients and in age 51-70 years,6/56 patients had wound dehiscence. Conclusion: In laparotomy patients, abdominal wound dehiscence is prominent obstacle that can be noticed pre operatively and genuine measurements should be taken to lessen its frequency. Keywords: Wound dehiscence, laparotomy, peritonitis